Ethylenediurea Induces Hormesis in Plants - Evgenios Agathokleous; Mitsutoshi Kitao (SAGE Publishing, 2018)
Tropospheric ozone levels are elevated throughout the northern hemisphere. The potential threat of ozone to vegetation urges for studying plant protection methods. The chemical ethylenediurea (EDU) is the most extensively utilized substance for protecting plants against ozone damage in research projects. This commentary provides collective evidence showing hormetic responses of plants to EDU and suggests that EDU may act as a conditioning agent against elevated ozone exposures. This article also suggests testing different substances in a hormetic framework for protecting plants against ozone damage. The concept of hormesis provides a significant perspective for reducing the economic cost for plant protection.